Fostering Deep Learning in Students: An AI Empowerment Program for Mathematics Teachers - zilrahmi zilrahmi; sri wahyu (Pelita Eksakta, 2026)
The advancement of Artificial Intelligence (AI) and deep learning offers significant opportunities for innovation in education. This program aimed to improve the understanding and skills of junior high school mathematics teachers in Padang City in utilizing AI to support creative and efficient learning. The training, held at SMP Negeri 25 Padang and attended by 55 MGMP Mathematics members, included lectures, hands-on practice using MagicSchool AI and ChatGPT, and the development of interactive learning media through Wordwall and Kahoot!. Evaluation results showed that all participants improved their understanding of AI and deep learning concepts, and more than 90% found the materials relevant and easy to apply. The training successfully fostered teachers’ motivation to adapt to AI-based learning innovations. Similar programs are recommended to continue with classroom mentoring to ensure optimal AI implementation in schools